Haematometra in one half of the uterus or rudimentary horn? - Rawal, Suniti; Baral, Josie; Singh, Meeta; Khan, Samira; Shakya, Beemba; Choudhary, Rashmi; Thapa, Mira; Anand, Varsha (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> A unicornuate uterus with functioning and non communicating rudimentary horn is a rare Mullerian abnormality, difficult to diagnose at times usually low in the list of differential diagnosis for pelvic pain and dysmenorrhea. A 22 years P1 presented with severe lower abdominal pain and dysmenorrhoea, following laparotomy that was done for endometriotic cyst of left ovary 7 months back. Radiographic studies revealed the haematometra in the rudimentary horn with normal uterus, right ovary and the tube. Laparotomy with drainage of haematometra and excision of septum along with the reconstruction of uterine cavity was performed thus anatomizing it with the cavity of the rudimentary horn. Both the intra and the post operative period were uneventful. She was discharged on OCP along with the advice to follow up regularly. She is asymptomatic till date. Key words: Endometriosis, haematometra, rudimentary horn doi:10.3126/njog.v2i1.1480 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 59 - 62 May -June 2007